2016
DOI: 10.1007/s00455-015-9678-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Training Effects of Two Swallowing Rehabilitation Therapies Using Surface Electromyography—Chin Tuck Against Resistance (CTAR) Exercise and the Shaker Exercise

Abstract: In this study, the efficacy of two dysphagia interventions, the Chin Tuck against Resistance (CTAR) and Shaker exercises, were evaluated based on two principles in exercise science-muscle-specificity and training intensity. Both exercises were developed to strengthen the suprahyoid muscles, whose contractions facilitate the opening of the upper esophageal sphincter, thereby improving bolus transfer. Thirty-nine healthy adults performed two trials of both exercises in counter-balanced order. Surface electromyog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
2
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 37 publications
2
67
2
10
Order By: Relevance
“…By contrast, the amount of load in the Shaker exercise is not easily quantifiable, and cannot be manipulated progressively over the course of treatment . Moreover, the sternocleidomastoid muscles are probably significantly more activated and fatigued during the Shaker exercise than during the SEA exercises . As swallowing is a submaximal activity, whereby increase in muscle volume is not the focal point, for the current study, a resistive load of approximately 60%‐70% of the estimated 1RM was maintained as the resistance level.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…By contrast, the amount of load in the Shaker exercise is not easily quantifiable, and cannot be manipulated progressively over the course of treatment . Moreover, the sternocleidomastoid muscles are probably significantly more activated and fatigued during the Shaker exercise than during the SEA exercises . As swallowing is a submaximal activity, whereby increase in muscle volume is not the focal point, for the current study, a resistive load of approximately 60%‐70% of the estimated 1RM was maintained as the resistance level.…”
Section: Discussionmentioning
confidence: 86%
“…32 Moreover, the sternocleidomastoid muscles are probably significantly more activated and fatigued during the Shaker exercise than during the SEA exercises. 42 As swallowing is a submaximal activity, 32 whereby increase in muscle volume is not the focal point, for the current study, a resistive load of approximately 60%-70% of the estimated 1RM was maintained as the resistance level. Besides, in this population of patients with head and neck cancer with chronic, severe dysphagia, hypertrophy is not expected.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control group, the experimental group showed a significant decrease in aspiration. Previous studies have demonstrated that CTAR exercise is an effective method to activate the suprahyoid muscles, using surface electromyography . The activation of more muscle fibres is likely to generate more power by recruiting more motor units.…”
Section: Discussionmentioning
confidence: 99%
“…1), while sitting, in order to strengthen the same submental muscles as those targeted in the HLE; hence, the expected effect is similar to that of HLE. Sze et al (11) demonstrated that CTAR exercise is more efficient than HLE because it the activates submental muscles similar to or higher than the HLE. As a result, patients were able to perform the exercise more easily than HLE, and the drop-out rate, which was moderate, also decreased.…”
Section: Interventionmentioning
confidence: 99%